2002
DOI: 10.1046/j.1475-1313.2002.00036.x
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of coloured lenses for age‐related macular degeneration

Abstract: The subjective benefit of coloured lenses appears to be due to a minor enhancement of contrast sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 37 publications
0
24
0
1
Order By: Relevance
“…Whether the implantation of a yellow IOL is indicated has been extensively discussed in several reviews. 18,[30][31][32][33] It is still not certain whether the potential optical side effects of blue-light-filtering IOLs can be accepted in exchange for a theoretical gain in retinal protection. The potential negative effect on color vision 20,34 was not confirmed in clinical studies in patients with yellow IOLs.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the implantation of a yellow IOL is indicated has been extensively discussed in several reviews. 18,[30][31][32][33] It is still not certain whether the potential optical side effects of blue-light-filtering IOLs can be accepted in exchange for a theoretical gain in retinal protection. The potential negative effect on color vision 20,34 was not confirmed in clinical studies in patients with yellow IOLs.…”
Section: Discussionmentioning
confidence: 99%
“…For non‐visual function, a number of studies have shown that yellow BBLs can be helpful for the treatment of insomnia, mood disorders, mania and delayed sleep phase disorder . For visual function, yellow BBLs have been recommended for ophthalmic purposes to correct the quality of vision for low‐vision patients, and in AMD patients, to enhance contrast sensitivity . Additionally, such BBLs are commonly used for outdoor visual tasks such as shooting, night driving, flying and skiing to enhance visual performance, especially under low visibility conditions of dusk, haze, and high luminance environments …”
mentioning
confidence: 99%
“…142 Colour vision was relatively unaffected by the use of coloured lenses in subjects with AMD. 152 A similar study using young patients revealed a systematic detriment to colour vision with increasing cut-off wavelength of the yellow lenses.…”
Section: Filtering Blue Light: the Use Of Yellow Filtersmentioning
confidence: 86%